2011
DOI: 10.1111/j.1365-2494.2011.00829.x
|View full text |Cite
|
Sign up to set email alerts
|

An alternative rotational stocking management designed to favour butterflies in permanent grasslands

Abstract: Grassland butterflies are on the decline throughout Europe. We tested an 'alternative rotational stocking' (ARS) strategy based on theoretical and practical aspects of grassland ecology, designed to increase butterfly diversity while also meeting farmers' production objectives. This management strategy implies taking animals away from one subplot of the rotation during the main flowering period. Its feasibility and benefits on butterfly diversity were tested by comparing ARS with continuous stocking (CS) in pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
2
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 51 publications
(65 reference statements)
1
21
2
3
Order By: Relevance
“…Nevertheless, while multi-taxon approaches have been largely applied to compare variations in diversity and abundance for various insect groups at variable grazing pressures Sjödin et al, 2008;Wallis De Vries et al, 2007), the simultaneous effects of different grazing systems and grazer species on a given plant community have, to date, been only scantily evaluated. focused only on sheep grazing and observed that a particular rotational grazing system, with sheep exclusion from pasture during the main flowering period as proposed by Farruggia et al, (2012), was more beneficial for bumblebees than it was for butterflies. Zhu et al (2015) focused on rationed grazing system with cattle, sheep and goats and recorded different responses of six insect groups (grasshoppers, homopterans, beetles, dipterans, hemipterans and butterflies) according to the grazer species, without considering grassland or animal performance during the grazing season.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, while multi-taxon approaches have been largely applied to compare variations in diversity and abundance for various insect groups at variable grazing pressures Sjödin et al, 2008;Wallis De Vries et al, 2007), the simultaneous effects of different grazing systems and grazer species on a given plant community have, to date, been only scantily evaluated. focused only on sheep grazing and observed that a particular rotational grazing system, with sheep exclusion from pasture during the main flowering period as proposed by Farruggia et al, (2012), was more beneficial for bumblebees than it was for butterflies. Zhu et al (2015) focused on rationed grazing system with cattle, sheep and goats and recorded different responses of six insect groups (grasshoppers, homopterans, beetles, dipterans, hemipterans and butterflies) according to the grazer species, without considering grassland or animal performance during the grazing season.…”
Section: Introductionmentioning
confidence: 99%
“…At the present stage, it is impossible to conclude whether the apparently contrasting effects of subplot exclusion found in this survey result mainly from a livestock species effect (Stewart and Pullin 2008) or from a grazing intensity effect. Cattle exclusion indeed produced a weak benefit that was limited to butterfly density when the two management strategies were compared in lightly-grazed plots (Farruggia et al 2012). Here, the butterfly assemblage was dominated by Maniola jurtina and Melanargia galathea, two species from tall grasslands that use grasses as larval host plants (Tolman and Lewington 1997).…”
Section: Discussionmentioning
confidence: 96%
“…However, as the two years during which this survey was conducted were favourable to grass growth, sward was also tall in CG plots and sward heterogeneity remained similar between RG and CG treatments. In another upland pasture, Farruggia, et al (2012) reported that excluding cattle from 25 % of plot areas during the main flowering period led to a 2.6-fold increase in butterfly abundance and a 2-fold increase in butterfly species richness relative to plots continuously grazed at the same high stocking rate. At the present stage, it is impossible to conclude whether the apparently contrasting effects of subplot exclusion found in this survey result mainly from a livestock species effect (Stewart and Pullin 2008) or from a grazing intensity effect.…”
Section: Discussionmentioning
confidence: 97%
“…One of the most effective ways for the conservation for endangered butterflies through meadow management is rotational mosaic mowing, usually complemented by extensive grazing as described below (Saarinen and Jantunen 2005;Farruggia et al 2012). Rotational mosaic mowing implies successive mowing of different meadow fragments (Morris and Rispin 1987;Saarinen and Jantunen 2005;Novák et al 2007;Gaisler et al 2011).…”
Section: Favourable Management Rotational Mowingmentioning
confidence: 99%